2012
DOI: 10.3390/cryst2030984
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic Metal—Antiferromagnetic Insulator Transition in π-d System λ-BETS2FeCl4, BETS = Bis(ethylenedithio)tetraselenafulvalene

Abstract: Quasi-two-dimensional organic conductor λ-BETS 2 FeCl 4 (BETS = bis(ethylenedithio)tetraselenafulvalene) transforms from a paramagnetic metal (PM) to an antiferromagnetic insulator (AFI) at a transition temperature, T MI , of 8.3 K under zero magnetic field. To understand the mechanism of this PM-AFI phase transition, we studied the thermodynamic properties of λ-BETS 2 FeCl 4 . We observed, below T MI , a six-level Schottky hump in its specific heat and a broad shoulder in its magnetic susceptibility. Just bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Recently, we found a six-level Schottky hump in the specific heat of -BETS2FeCl4 system in the AFI phase [7][8][9], where Tokumoto reported that the magnetic susceptibility decreases rapidly with an anomalous shoulder [5]. Just below the TMI, approximately 80 % of the 3d spin degree of freedom remain free.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, we found a six-level Schottky hump in the specific heat of -BETS2FeCl4 system in the AFI phase [7][8][9], where Tokumoto reported that the magnetic susceptibility decreases rapidly with an anomalous shoulder [5]. Just below the TMI, approximately 80 % of the 3d spin degree of freedom remain free.…”
Section: Introductionmentioning
confidence: 94%
“…However, Akiba et al performed specific heat measurements for λ-(BETS) 2 FeCl 4 and revealed that the 3d spin system shows a Schottky-like anomaly in the magnetic heat capacity below T N , and they suggested that the localized π electron system undergoes an AF ordering at T N , while the 3d spin system maintains a paramagnetic state under the effective magnetic field arising from the π−d interaction. 27 . However, the AF ordering state had not been found in λ-type systems with nonmagnetic anions.…”
mentioning
confidence: 99%
“…Such situation characteristic in the -d interacting system changes the three-dimensional ordered state to the unconventional magnetic state such that the nature of the one-dimensional direct magnetic interaction remains even below TN. Interestingly, the similar hump structure is also observed more clearly in the -(BETS)2FeCl4, which is another-d interacting system, which is reviewed in [56]. Recently, some theoretical studies on the emergence of the hump structure in the -d interacting system have been reported [57].…”
Section: Crystals 2018 8 X For Peer Review 7 Of 15mentioning
confidence: 68%